Development of energy benchmarks for office buildings using the national energy consumption database - Kim, Hye Gi; Kim, Sun Sook (Energies, 2020)
In an effort to improve the energy efficiency of existing buildings, it is necessary to first evaluate the energy performance of those buildings. Since it is difficult to obtain detailed information on existing buildings, the challenge is how to conduct reliable energy performance assessments with this limited information. As a result, many countries have adopted evaluation systems based on measured energy consumption data for existing buildings. This study aims to analyze the building energy consumption and characteristics using Korea's national building database and provide an energy performance benchmark for continuous management of the energy performance of existing buildings. We analyzed the relationship between the basic statistical characteristics of the information collected from the national integrated energy database and energy consumption. The total floor area was found to be closely related to energy consumption, and various regression analysis methods were applied and compared to develop a benchmark to explain the trends of energy consumption according to the increase in total floor area. Finally, the developed benchmarks were used to evaluate energy consumption and examine the feasibility of the benchmarks.
Keywords: Building energy; Building energy consumption; Energy benchmarks; Energy performance; Limited information; Measured energy consumption; Regression analysis methods; Statistical characteristics; Building energy benchmarking; Energy performance benchmark; Existing building; Office building